Os limites entre os valores militares e os direitos fundamentais: repercussões das restrições à liberdade de expressão, à vida privada e à saúde mental sobre a identidade profissional e a dignidade do policial militar estadual. - Rogério da Rocha dos Santos; Hugo Gonzaga Silva Dias; Leandro Chavier Soares; Fábio dos Santos Leal (Revista ft, 2026)
This article discusses the antinomies between the constitutional principles of protection of fundamental rights and the military values of hierarchy and discipline, structuring the state Military Police. The research problem focuses on understanding how the normative mitigation of these rights affects the identity and dignity of military police officers, focusing on restrictions on freedom, mental health and private life. The general objective is to examine the consequences of this legal duality in the life of the public security agent, analyzing the possibilities of conciliation. The research adopted the methodology of literature review, with a qualitative approach and descriptive character, based on doctrinal works, scientific articles and subsidiary analysis of legislation and jurisprudence in the light of the doctrine. The development showed that, although the regime of special subjection has constitutional ballast, its practical application often transgresses the essential core of human dignity, resulting in chronic psychic illness, high rates of stress and depression, in addition to the systematic invasion of the policeman's free time. It has been shown that the hermeneutic technique of proportionality proves insufficient to manage the suffering generated by a totalizing organizational culture. It is concluded, supported by the literature and recent federal legislative debates, that the conciliation between operational efficiency and the protection of the human being permeates the reflection on the delimitation of the functional journey (right to disconnection), the valorization of psychosocial support and the improvement of military education, overcoming the paradigm of silencing in favor of the training of a citizen security professional and subject of rights.Keywords: Public Security; Climate; Social Responsibility; COP30; Urban Mobility.